STRATEGIC PARTNERSHIP MODEL FOR SUSTAINABLE EMPOWERMENT BETWEEN COMPANIES AND COMMUNITIES IN THE NICKEL MINING REGION OF KOLAKA REGENCY - abdul sabaruddin; Ahmad Zul Fikri; Fitri Syawalia; Winda Septemi Patibong (Journal of Social Politics and Governance (JSPG), 2026)
Partnerships between companies and communities are crucial for empowering communities in mining areas. However, in Kolaka Regency, these partnerships have not been implemented optimally or sustainably. This is evident from low community participation, weak coordination among stakeholders, short-term program initiatives, and a lack of partnership models tailored to local needs. This study utilizes partnership theory, which includes pseudo-partnerships, mutualistic partnerships, and conjugative partnerships. This study aims to analyze and develop a model for strategic partnerships between companies and communities in sustainable empowerment programs within the nickel mining area of Kolaka Regency. It employs a qualitative approach that includes interviews, observations, and documentation. The research findings indicate that partnerships between companies and communities are often superficial, as planning and decision-making processes have not been conducted collaboratively. As a result, empowerment programs are not fully aligned with community needs and lack sustainability. Additionally, these partnerships exhibit semi-productive characteristics that are short-term in nature and lack a vision for sustainable development. Local governments need to facilitate multi-stakeholder partnerships among mining companies, communities, government, and academics. This approach will strengthen coordination and empower communities based on research and local needs in a participatory and sustainable manner.